Clinical utility of proteinase 3-antineutrophil cytoplasmic antibody at diagnosis in predicting subsequent relapse in patients with microscopic polyangiitis - Ha, Jang Woo; Kwon, Oh Chan; Park, Yong-Beom; Lee, Sang-Won (Frontiers in Medicine, 2026)
BackgroundIn real clinical practice, patients classified as microscopic polyangiitis (MPA) according to the new 2022 criteria, despite proteinase 3 (PR3)-antineutrophil cytoplasmic antibody (ANCA) positivity, are occasionally encountered. Hence, this study investigated the clinical utility of PR3-ANCA detected at diagnosis in MPA patients.MethodsWe included 191 patients with MPA in this study and retrospectively reviewed their medical records, in which clinical data at diagnosis and during follow-up were recorded. Additionally, we investigated three major poor complications of MPA, such as subsequent all-cause mortality (ACM), relapse, and end-stage kidney disease (ESKD). Cumulative survival rates were compared among the groups using Kaplan–Meier survival analysis with the log-rank test.ResultsAt diagnosis, the median age of 191 MPA patients was 64 years (68 males and 123 females). PR3-ANCA was detected in only 10 patients (5.2%). During follow-up, among the 191 MPA patients, 32 patients died, 43 patients experienced subsequent relapse, and 39 progressed to ESKD. In the comparative analyses, at diagnosis, PR3-ANCA-positive MPA patients were younger and had lower white blood cell count and blood urea nitrogen levels than PR3-ANCA-negative patients. During follow-up, PR3-ANCA-positive MPA patients showed a higher frequency of subsequent relapse than PR3-ANCA-negative patients. Additionally, in Kaplan-Meier survival analysis, PR3-ANCA-positive MPA patients exhibited a significantly lower relapse-free survival rate than PR3-ANCA-negative patients over the follow-up period.ConclusionIn this study, we found that PR3-ANCA positivity at diagnosis is significantly associated with subsequent relapse in patients with MPA during follow-up.